KESIAPAN GURU MADRASAH DI KOTA SEMARANG DALAM MENGHADAPI PELAKSANAAN PPG - Farikh, Amin (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractProfessional Teacher Education (PTE/ PPG) can be regarded as a program to improveÂ the competence of todayâs most important teacher. This program is not solely theÂ learning process of the teachers, but also as a starting point increase teachersâ welfareÂ through the provision of teaching certi" cate and allowances. However, the level ofÂ preparedness of teachers to plan the holding of Professional Teacher EducationÂ (PTE/ PPG) is still low. The mechanism and all the provisions of the ProfessionalÂ Teacher Education (PTE/ PPG) is not understanded, the teacher could not prepareÂ him to adapt. Therefore, the implementation of Professional Teacher Educationshould involve at least four (4) It is important to note ; First, Improved readiness andÂ support of teachers. Second, socialization widely. Third, the accuracy of the allocationÂ of time. Fourth, the full support of the government. If the four components are metÂ then automatically readiness of teachers on the implementation of Professional TeacherÂ Education (PTE/ PPG) will go well.